Adopting a Blended Leadership Approach: Navigating Crisis in Supermarkets during the COVID-19 Pandemic - Bux, Naadirah; Mkhize, Msizi Vitalis; Suknunan, Sachin (New Advances in Business, Management and Economics Vol. 4, 2025)
The COVID-19 pandemic significantly affected the supermarket sector, placing immense pressure on leaders to ensure operational continuity and employee motivation. This paper examines the leadership style that was most effective and preferred by supermarket employees, during the COVID-19 pandemic, in the Pietermaritzburg area of KwaZulu-Natal, South Africa. The research adopted a qualitative approach with a purposeful sampling of 10 participants and thematic analysis was conducted on collected data. The primary findings indicated that before the pandemic, leaders primarily adopted transformational, transactional, democratic and autocratic leadership styles. However, the pandemic forced leaders to consider a more adaptive leadership style and the results highlighted the importance of having a blend of adaptive, democratic and transformational leadership. This blend was also preferred by employees in relation to employee motivation, collaboration and flexibility which in turn helped them to navigate challenges and maintain morale. The research concluded that no single leadership style suffices during crises, instead, a blend of adaptive, democratic and transformational leadership styles proved most effective in maintaining employee morale and organisational continuity during the crisis and achieving organisational goals. This blend of leadership approaches can also help navigate future crisis situations and promote organisational continuity. The research contributes to understanding leadership adaptation in smaller supermarket settings, highlighting the importance of adjusting leadership styles in response to employee needs in crisis situations. These insights can serve as a leadership framework for managing future crises in small-to-medium enterprises.